Estimation of inferior alveolar nerve proximitytothe root api-ces : A CBVI analysis - Pagare, Sandeep; Roy, Christine; Vahanwala, Sonal; Gavand, Kapil; Waghmare, Mandavi; Goyal, Saurabh (Journal of Oral and Dental Sciences, 2018)
A sound knowledge of the relative three dimensional (3D) approximations to the inferior alveolar nerve (IAN) to the root apices of the mandibular premolars and molars and their significance to gender and age is imperative for any dental procedure. Utilization of Cone Beam Computed Tomography (CBCT) has facilitated increased accuracy, higher resolution, and scan time and dose reduction. Literature reveals that various procedures in endodontics and oral surgery may lead to IAN injury, a rare but serious treatment complication. It can result from over instrumentation, periapical surgery and over filling by root canal obturation materials. Surgical endodontic procedures require a thorough knowledge of anatomic structures that might be traumatized. What better view than CBCT, where it gives a thorough knowledge about the 3D position of the IAN, allowing 3D reconstruction in true 1:1 anatomic representation. Majority of IAN injury cases reported were in relation to the mandibular second molars hence before undertaking procedures with potential damage to the IAN, it is essential to know the location of the IAN with respect to the surrounding structures to avoid injury or harm. A study was undertaken with an aim to assess the distance between the apical tips of the mesial roots of the first, second molars and second premolars to the superior border of the IAN. The findings of which could be used to prevent injuries to the inferior alveolar nerve.